Clinical CDK4/6 inhibitors induce selective and immediate dissociation of p21 from cyclin D-CDK4 to inhibit CDK2 - Pack, Lindsey R. (Nat Commun, 2021)
Since their discovery as drivers of proliferation, cyclin-dependent kinases (CDKs) have been considered therapeutic targets. Small molecule inhibitors of CDK4/6 are used and tested in clinical trials to treat multiple cancer types. Despite their clinical importance, little is known about how CDK4/6 inhibitors affect the stability of CDK4/6 complexes, which bind cyclins and inhibitory proteins such as p21. We develop an assay to monitor CDK complex stability inside the nucleus. Unexpectedly, treatment with CDK4/6 inhibitors—palbociclib, ribociclib, or abemaciclib—immediately dissociates p21 selectively from CDK4 but not CDK6 complexes. This effect mediates indirect inhibition of CDK2 activity by p21 but not p27 redistribution. Our work shows that CDK4/6 inhibitors have two roles: non-catalytic inhibition of CDK2 via p21 displacement from CDK4 complexes, and catalytic inhibition of CDK4/6 independent of p21. By broadening the non-catalytic displacement to p27 and CDK6 containing complexes, next-generation CDK4/6 inhibitors may have improved efficacy and overcome resistance mechanisms.